Therapy Effect of Ethanol Extract of Binahong Tuber on Superoxide Dismutase (SOD) of Kidney of Rat Induced by Alloxan - Ummah, Silviana Maslakhatul; Hasanah, Hafidatul (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
Binahong (Anredera cordifolia (Ten.)Steenis) tuber is one of the plant that is not utilized yet for medicine. The aims of this research are to extract Binahong tuber Â and determine superoxide dismutase (SOD) activity of kidney of rat (RattusNorvegicus) induced by Aloxsan. Extraction of binahong tuber was conducted by maceration method using 70% ethanol. The ethanol extract was used for therapy of Rat induced by Aloxsan and to determine SOD activity. Measuring of SOD kidney activity was conducted on 6 group of rat are D1 (control), D2 (0,5 % CMC-Na, dose 1 mL/200 g body weight), D3 (aloxsan 32 mg/200g body weight), D4, D5, D6 (aloxan 32 mg/kg body weight with therapy. Doses of extract binahong tuber were 25, 50 and 75 mg/kg body weight, respectively.The results showed that therap y of 70 % ethanol extract of Binahong tuber could increase the SOD activity of rat kidneys. But, after analyzed by ANAVA one way, the therapy did not give a real effect with value of Î±0,05 (0,1290,05). Duncan test showed that there was significant difference between D3 and D4. So the effective dose was 25 mg/kg body weight. Phytochemical test showed that ethanol extract of binahong tuber contained alkaloid, flavonoid, saponin, tanin and terpenoid.Â Keywords: Tuber of Anredera cordifolia (Ten.) Steenis, Superoxide Dismutase, Alloxan